Adaptation patterns and cultural change of Batak Toba migrants in Pematangsiantar city - Corry Corry; Ulung Napitu; Ease Arent; Sunggul Gultom; Abdul Muis; Muhammad Gazali Bancin (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
This study examines the pattern of adaptation and socio-cultural change of Toba Batak migrants in Pematangsiantar City. The territorial mobility of Toba Batak migrants, which is permanent and expansionist, affects their adaptation patterns, socio-cultural changes, and settlements after they become migrants in new areas. The method used to analyze data about the pattern of adaptation and socio-cultural change of the Toba Batak people used descriptive qualitative methods. Through this method, it is hoped that it will be able to answer research problems. The population in this study were all Toba Batak migrants living in Pematangsiantar City. Informants in this study were 12 people consisting of 5 people from Toba Batak traditional leaders and one person for comparison with Simalungun traditional leaders, one person in Angkola, one person for Javanese, one person for Malay, one person for Mining, one person for Karo, and one person for Chinese. . Data were collected through in-depth interviews combined with library data. The results of the interviews were collected, tabulated, analyzed, verified, and displayed to conclude. The results showed that the pattern of adaptation and socio-cultural change experienced by Toba Batak migrants was influenced by the cultural background of Pematangsiantar City, namely Simalungun culture as the host culture, and other cultures that were not dominant. Toba Batak migrants adapt in Pematangsiantar City to local culture but retain most of their socio-cultural values, even though they become migrants and settle in Pematangsiantar City